Incidence and predictors of acute kidney injury among traumatic brain injury patients in Northwest Ethiopia: a cohort study using survival analysis - Zelalem Alamrew Anteneh; Semew Kassa Kebede; Abebaw Gedef Azene (BMC Nephrology)
Abstract Background Acute kidney injury (AKI) is a sudden and reversible decrease in kidney function, causing the retention of waste products in the blood and potentially resulting in severe complications or death if not timely managed. Studies on AKI among traumatic brain injury patients in low-income nations like Ethiopia is very critical due to the limited healthcare resources, high burden of trauma-related injuries, and lack of robust data on the incidence and risk factors of AKI in such settings, which hinders effective prevention and treatment strategies tailored to these vulnerable populations Therefore, this study aimed to assess the incidence and predictors of AKI among traumatic brain injury patients. Methods A retrospective cohort study was conducted among 450 adult patients with traumatic brain injuries admitted to Tibebe-Ghion Specialized Hospital in Ethiopia. Kaplan- Meir curve and Log rank test were used to estimate and compare survival probability of different categories. A multivariable Cox proportional hazards model was used to identify determinants of acute kidney injury (AKI). Results The incidence of AKI was 10.9%, with a median follow-up period of 42 days. Significant predictors of AKI among traumatic brain injury patients included age (AHR: 1.05, 95% CI: 1.02–1.07), severe head injury (AHR: 1.46, 95% CI: 1.02–2.09), unreactive pupillary response (AHR: 4.82, 95% CI: 1.82–12.72), and hypotension (AHR: 3.45, 95% CI: 1.71–6.96). Conclusions The study found that AKI occurs in more than one in ten patients with traumatic brain injuries, with significant predictors including older age, severe head injury, unreactive pupillary response, and hypotension. These findings highlight the need for careful monitoring and early intervention for high-risk patients to prevent AKI and improve overall outcomes. Implementing targeted prevention and treatment strategies in settings with limited resources can help mitigate the burden of AKI and enhance patient care in vulnerable populations.